2018
DOI: 10.1002/mrm.27216
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative susceptibility mapping of articular cartilage: Ex vivo findings at multiple orientations and following different degradation treatments

Abstract: PurposeWe investigated the feasibility of quantitative susceptibility mapping (QSM) for assessing degradation of articular cartilage by measuring ex vivo bovine cartilage samples subjected to different degradative treatments. Specimens were scanned at several orientations to study if degradation affects the susceptibility anisotropy. T2*‐mapping, histological stainings, and polarized light microscopy were used as reference methods. Additionally, simulations of susceptibility in layered geometry were performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 53 publications
(76 reference statements)
0
46
0
Order By: Relevance
“…Despite the idealised ex vivo experimental set up, the work presented here highlights the promise for DTI metrics to yield valuable insight into arterial microstructure which could ultimately provide novel insight into diseased tissue morphologies. For example, recent in vivo studies have used quantitative susceptibility mapping to investigate gross morphological features [69][70][71] and inflammation 72 in atherosclerotic plaques, but this approach also has potential to provide markers of tissue microstructure and integrity 73 . Ideally, a combination of methods which allow for the full characterisation of the microstructure within the vessel wall would provide the insight needed to better inform the risk of atherosclerotic plaque rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the idealised ex vivo experimental set up, the work presented here highlights the promise for DTI metrics to yield valuable insight into arterial microstructure which could ultimately provide novel insight into diseased tissue morphologies. For example, recent in vivo studies have used quantitative susceptibility mapping to investigate gross morphological features [69][70][71] and inflammation 72 in atherosclerotic plaques, but this approach also has potential to provide markers of tissue microstructure and integrity 73 . Ideally, a combination of methods which allow for the full characterisation of the microstructure within the vessel wall would provide the insight needed to better inform the risk of atherosclerotic plaque rupture.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study investigated the feasibility of QSM and normalT2*‐mapping for assessing degradation of articular cartilage by measuring ex vivo bovine cartilage samples subjected to different degradative treatments . They found that the susceptibility anisotropy of the cartilage differed from the normalT2* anisotropy.…”
Section: Discussionmentioning
confidence: 99%
“…24 Other techniques such as polarized light microscopy can also be used to detect the collagen fibril orientation of knee cartilage. 34 QSM is valuable in assessing early OA, as it provides specific information on the distribution and content of collagen fibrils in cartilage. 34 We are currently investigating the ability of QSM to study the susceptibility changes of knee in aging in a large cohort, as these changes are potentially important to initiate early treatment, monitor disease progression, and follow-up of operative cartilage repair.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D GRE datasets acquired at 9.4 T MRI were processed for quantitative susceptibility mapping (QSM) to visualize the vascular structures in the cartilage canals using an approach similar to that previously described . The QSM processing consisted of first manually creating a mask for the articular‐epiphyseal cartilage complex (AECC) using ITK‐SNAP (http://www.itksnap.org).…”
Section: Methodsmentioning
confidence: 99%
“…The 3D GRE datasets acquired at 9.4 T MRI were processed for quantitative susceptibility mapping (QSM) to visualize the vascular structures in the cartilage canals using an approach similar to that previously described. 15,[17][18][19] The QSM processing consisted of first manually creating a mask for the articular-epiphyseal cartilage complex (AECC) using ITK-SNAP (www.itksnap.org). Subsequently, the field map was calculated from the phase data in the masked region utilizing Laplacian unwrapping (cutoff frequency = 10 −10 ) 20 followed by variable-kernel sophisticated harmonic artifact reduction for phase data (V-SHARP) background field removal (the SHARP threshold was set to 0.5 and kernel radius varied between 2 and 9).…”
Section: Image Processingmentioning
confidence: 99%